Efficient conservation in a utility-maximization framework - Davis, F. W.; Costello, C. J.; Stoms, D. M. (Ecology and Society, 2006)
Systematic planning for biodiversity conservation is being conducted at scales ranging from global to national and regional. The prevailing planning paradigm is to identify the minimal land allocations needed to reach specified conservation targets or for maximizing the amount of conservation accomplished under an area or budget constraint. We propose a more general formulation for setting conservation priorities that involves goal setting, assessing the current conservation system, and estimating the contribution of a site to overall utility. Under this new formulation of the problem, the value of a site depends on resource quality, threats to resource quality, and costs. We allocate available conservation funds to sites to maximize the overall utility of the regional conservation system, expressed in terms of the biodiversity remaining at the end of the planning period. The planning approach is designed to support collaborative processes and negotiation among competing interest groups. We demonstrate these ideas with a case study of the Sierra Nevada Bioregion of California.
Keywords: Biodiversity conservation planning California cost-effectiveness scenario marginal conservation value retention